Correlation between eosinophils and aminotransferases among patients with and without diabetes from a polyclinic in the district of Villa El Salvador, Lima, Peru - Guevara Tirado, Alberto (2024)
Objective: To determine the correlation between eosinophil count and aminotransferase levels among patients with and without diabetes from a polyclinic in the district of Villa El Salvador. Materials and methods: An observational, analytical and correlational study was conducted with 767 individuals, out of which 500 were patients without diabetes and 267 were patients diagnosed with diabetes mellitus for at least six months and undergoing treatment. The study variables included age, sex, basal glycemia, eosinophil count, aspartate aminotransferase (AST) levels and alanine aminotransferase (ALT) levels. The Kolmogorov-Smirnov test was used to assess normality and Spearman’s correlation coefficient was applied. The cut-off point for statistical significance was set at α = 0.05. Data analysis was performed using IBM Statistical Package for Social Sciences Statistics 25.0 software for Windows. Results: Among patients without diabetes, elevated AST and ALT levels were observed in 46.40 % and 27.20 %, respectively. In contrast, 62.50 % of patients with diabetes had elevated AST levels, while 35.50 % had elevated ALT levels. Among patients with diabetes, a moderate and negative correlation between eosinophil differential count and AST (Rho = -0.665) and ALT (Rho = -0.586) levels was found, whereas the group of patients without diabetes showed a weak or null correlation. Conclusions: Eosinophil count is moderately and negatively correlated with aminotransferase levels among patients with diabetes. Given the study limitations and the lack of direct precedents, further research with larger populations are needed. The interaction between polymorphonuclear cells, such as eosinophils, and hepatic and systemic inflammatory markers, such as aminotransferases, may serve as an early pathophysiological indicator of diabetes mellitus, potentially years or decades before the onset of micro- and macrovascular systemic complications of this endocrinopathy.